Collective Management of Rights in Streaming Platforms - Barros, Carolina Geissler Miranda de (2016)
This work intends to present a legal panorama of the discussions involving the collective management of copyright and the musical streaming platforms in Brazil, considering the technological revolution and the changes in the consumption of entertainment products, specifically related to the Phonographic market. Content analysis was used through indirect documentation to identify recent changes in Brazilian legislation and trends evidenced by judicial decisions and official manifestations of the Ministry of Culture, in a clear conjuncture of major changes related to collective management.